KAJIAN PENGARUH KONSENTRASI ELEKTROLIT TERHADAP KINERJA BATERAI ISI ULANG PANi/H2SO4/PbO2 - Leonardo, Chandra; Kartawidjaja, Mariah; Alamsyah, Wahyu; Hidayat, Sahrul (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Polyaniline (PANi) is one of the conductive polymers that have special properties compared to the others. PANi have some advantages included the chemical and physical stability is excellent, redox reaction is reversible, the conductivity is wide range and PANi can be synthesized by chemical or electrochemical method. In this research, we have synthesis PANi by chemical methods and used it as electrodes in rechargeable battery system. The structures of battery system are PANi / H2SO4 / PbO2. PANi has been synthesized from aniline as monomer in the solvent of 1M H2SO4 and using ammonium peroxydisulfate as initiator. The Results of synthesis is brown powder in the form of emeraldine-base. The battery electrode is made from PANi powder by means of dissolved in the n-metilpirrolidinon (NMP) and deposited onto the Al-foil substrate. The cell of rechargeable battery is made from PANi and PbO2 electrode in the electrolyte of H2SO4. The focus of this research is study the battery performance of (PANi / H2SO4 / PbO2) with variations the concentration of electrolyte. The results of this research, we have demonstrated the open voltage of the battery system is about 2.1 Volts. The working voltage of battery is varying from 1.5 Volts to 2 Volt at loading with a constant current of 10 mA until 80 mA. The working voltage of battery is depending to the concentration of electrolyte. The working voltage is decreasing proportional to the lower concentrations of electrolytes. Keywords: Polyaniline (PANi), rechargeable battery, battery performance.